2010
DOI: 10.1002/med.20226
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Damaged DNA: Structure and Dynamic Markers

Abstract: DNA damage, a consequence of external factors and inherent metabolic processes, is omnipresent. Nature has devised multiple strategies to safeguard the genetic information and developed intricate repair mechanisms and pathways to reverse an array of different DNA lesions, including mismatches. Failure of the DNA repair systems may result in mutation, premature ageing, and cancer. In this review, we focus on structural and dynamic aspects of detection of lesions in base excision and mismatch repair. A thorough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 165 publications
0
28
0
7
Order By: Relevance
“…One single-stranded DNA genome is generated each time a double-stranded DNA genome is used as a template (Knipe, 2006). These DNA structures can stimulate a robust DNA-damage response (Germann et al, 2010; Peterson and Cote, 2004). We previously reported that viral genome replication leads to widespread phosphorylation of H2AX, suggesting that the infected cell experiences a diffusely distributed genotoxic signal (Nichols et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…One single-stranded DNA genome is generated each time a double-stranded DNA genome is used as a template (Knipe, 2006). These DNA structures can stimulate a robust DNA-damage response (Germann et al, 2010; Peterson and Cote, 2004). We previously reported that viral genome replication leads to widespread phosphorylation of H2AX, suggesting that the infected cell experiences a diffusely distributed genotoxic signal (Nichols et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that DNA-binding proteins can recognize differences in structures and flexibilities of DNA duplexes (1,2). X-ray crystallography and nuclear magnetic resonance (NMR) are powerful tools for analysis of DNA structures, but these techniques require a large amount of sample and are time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…For the short patch repair, the phosphodiester bond at 3′ of the abasic site is cleaved by glycosylate, and the 5′ bond is incised by APE1 endonuclease, which then recruits DNA polymerase to fill the gap that is ligated by a DNA-ligase complex. During the process of BER, the conformation and flexibility of DNA changes with the binding of different enzymes, which kinks the DNA to different angles [168][169][170][171][172][173][174][175]. Through careful design of experiments, the SSFM platform can potentially detect DNA BER through direct detection of DNA conformational changes and protein-binding events.…”
Section: Discussionmentioning
confidence: 99%